Pengaturan Laju Aliran FluidaUntuk Meningkatkan Laju Perpindahan Panas Pada Solar Water Heater Di Kota Pontianak - Rusadi, Rusadi (Faculty of Engineering, Universitas Tanjungpura, 2017)
Abstractâ€“Issues about the energy crisis and clean energy in the environment become an important issue. Energy that meets the above properties is solar energy. Utilization is highly dependent on climate and weather conditions in accordance with the geographical location of the place. Optimization of energy absorption needs to be done and this is usually done by conditioning or manipulating some parameters so that the level of energy absorption is more effective and efficient.This research is an expriment research by optimizing the absorption of heat energy to heat water according to climate and weather conditions in Pontianak, West Kalimantan. The variable to be conditioned or arranged so that the maximum heat transfer rate is the flow rate of the water fluid to be heated.The experimental results show that the water flow rate of 2450 ccm DHW Loop side for SHW has a temperature difference value on the exit side of the heat exchanger which is smaller than the others. This shows that the more effective the release and absorption of heat made by the fluid in the heat exchanger.Â Keywordsâ€“ Solar energy, Solar Water Heater (SHW), fluid flow rate, heat transfer rate